Accumulation of amyloid-β by astrocytes result in enlarged endosomes and microvesicle-induced apoptosis of neurons - Söllvander, Sofia; Nikitidou, Elisabeth; Brolin, Robin; Söderberg, Linda; Sehlin, Dag; Lannfelt, Lars; Erlandsson, Anna (Molecular neurodegeneration, 2016)
Despite the clear physical association between activated astrocytes and amyloid-β (Aβ) plaques, the importance of astrocytes and their therapeutic potential in Alzheimer's disease remain elusive. Soluble Aβ aggregates, such as protofibrils, have been suggested to be responsible for the widespread neuronal cell death in Alzheimer's disease, but the mechanisms behind this remain unclear. Moreover, ineffective degradation is of great interest when it comes to the development and progression of neurodegeneration. Based on our previous results that astrocytes are extremely slow in degrading phagocytosed material, we hypothesized that astrocytes may be an important player in these processes. Hence, the aim of this study was to clarify the role of astrocytes in clearance, spreading and neuronal toxicity of Aβ. To examine the role of astrocytes in Aβ pathology, we added Aβ protofibrils to a co-culture system of primary neurons and glia. Our data demonstrates that astrocytes rapidly engulf large amounts of Aβ protofibrils, but then store, rather than degrade the ingested material. The incomplete digestion results in a high intracellular load of toxic, partly N-terminally truncated Aβ and severe lysosomal dysfunction. Moreover, secretion of microvesicles containing N-terminally truncated Aβ, induce apoptosis of cortical neurons. Taken together, our results suggest that astrocytes play a central role in the progression of Alzheimer's disease, by accumulating and spreading toxic Aβ species.